Area Assessment of English in the Application of Edupreneurship in Convention and Event Business Management in a Public Tourism Polytechnic - Suparto, Windy Puspitasari; Lao, Yandres A. Dj.; Salim, Muhammad Arfin Muhammad (Naifaderu Cipta Sejahtera, 2023)
Purpose The purpose of this study was to identify, describe, and analyze the application of edupreneurship in convention and event business management for English classes at the Makassar State Tourism Polytechnic Methodology The qualitative descriptive method was used by researchers in this study. What is meant by